Voltage transient management for Alternating Current trains with vacuum circuit breakers - Thomas Moore; Felix Schmid; Pietro Tricoli (IET Electrical Systems in Transportation)
Abstract Alternating current power supplies and rolling stock with 25 kV (50 or 60 Hz) and 15 kV (16.7 Hz) traction systems do not have the characteristics and behaviour of a typical three‐phase medium‐voltage distribution system. Switching inductive loads with a vacuum circuit breaker (VCB) in MV traction systems poses familiar challenges as well as some unique challenges, such as the crossing of phase change neutral sections. Transformers represent highly inductive loads due to their iron core and, thus, the consequences of energizing and disconnecting a transformer and dealing with the energy stored in its inductance must be considered within a system context. The authors of this study consider two transient phenomena associated with switching single‐phase, medium voltage, AC traction transformer loads using a VCB on railway rolling stock: (i) switching transients that occur when disconnecting a transformer, particularly if lightly loaded and (ii) pre‐ignition and current inrush that occurs when energizing a transformer. Both phenomena can cause reliability problems, requiring increased system maintenance or resulting in premature failures of system components. The authors review the use of controlled switching and other state‐of‐the‐art methods to prevent or limit voltage transients when switching a transformer load by means of a VCB. The effective application of such techniques has been demonstrated in previous research or established in practical applications by manufacturers and electrical distribution network companies.